Patent Law and the Materiality of Inventions in the California Oil Industry: The Story of Halliburton v. Walker, 1935–1946. (29th March 2023) - Con Díaz, Gerardo
Abstract : This article examines a patenting conflict between the Halliburton Oil Well and Cementing Company and an independent inventor named Cranford Walker. It argues that Halliburton's effort to lower the barriers to entry into the oil well depth measurement industry facilitated the re-emergence of materiality as a pre-condition for the patent eligibility of inventive processes. In 1941, Walker sued Halliburton for infringement of three of his patents, and Halliburton responded with an aggressive defense aimed at invalidating them. Over the next five years, the courts handling this conflict adopted very narrow legal theories developed during the Second Industrial Revolution to assess the patent eligibility of inventions that involved mental steps—processes such as mathematical computations, which people can perform in their minds. The resulting legal precedent cleared the path for Halliburton's short-term industrial goals and continued to shape patent law for the rest of the century.